2003
DOI: 10.1007/s11664-003-0017-2
|View full text |Cite
|
Sign up to set email alerts
|

Sputtered copper films with insoluble Mo for Cu metallization: A thermal annealing study

Abstract: The thermal annealing behavior of Cu films containing insoluble 2.0 at.% Mo magnetron co-sputtered on Si substrates is discussed in the present study. The Cu-Mo films were vacuum annealed at temperatures ranging from 200°C to 800°C. X-ray diffraction (XRD) and scanning electron microscopy (SEM) observations have shown that Cu 4 Si was formed at 530°C, whereas pure Cu film exhibited Cu 4 Si growth at 400°C. Twins are observed in focused ion beam (FIB) images of as-deposited and 400°C annealed, pure Cu film, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 30 publications
1
46
0
2
Order By: Relevance
“…Our previous studies have indicated that the doping of insoluble substances in Cu films can inhibit recrystallization and grain growth, and thus the formation of copper silicide, during annealing. [7][8][9][10][11][12][13][14] We have further confirmed that annealing of Cu(W) 11 and Cu(Mo) 12 films for 1 h at 400°C yielded no copper silicide and had a low resistivity and high thermal stability. The aim of the current study is to investigate the thermal reliability of Cu(W) and Cu(Mo) films after annealing for long periods of time.…”
Section: Introductionsupporting
confidence: 62%
“…Our previous studies have indicated that the doping of insoluble substances in Cu films can inhibit recrystallization and grain growth, and thus the formation of copper silicide, during annealing. [7][8][9][10][11][12][13][14] We have further confirmed that annealing of Cu(W) 11 and Cu(Mo) 12 films for 1 h at 400°C yielded no copper silicide and had a low resistivity and high thermal stability. The aim of the current study is to investigate the thermal reliability of Cu(W) and Cu(Mo) films after annealing for long periods of time.…”
Section: Introductionsupporting
confidence: 62%
“…14 To keep a barrierless Cu alloy system's resistivity low, we need to add minute quantities of alloying elements or compounds to a Cu film. Our other studies 5,6,[13][14][15][16] also record our successful use of effective insoluble alloying elements or compounds, such as refractory and transition metals (W, Mo, Ru, etc.) and their nitrides, for Cu barrierless metallization.…”
Section: Introductionmentioning
confidence: 89%
“…When the device dimensions are reduced to a nanometer scale, the resistance of the entire device will increase, due to higher resistivity and a surface scattered with thin barriers. 2 A barrierless metallization method based on enhanced thermal stability in Cu alloys has been proposed [3][4][5][6][7][8][9][10][11][12][13][14][15][16] as an alternative solution. For example, Cu(RuN) doped on barrierless Si is reported to be stable at temperatures up to 680°C.…”
Section: Introductionmentioning
confidence: 99%
“…The copper silicide in the Cu(MoN x ) film is not observed until annealed at 580°C. The maximum stable temperature without copper silicide formation is thus 560°C, which is higher than those of 400°C and $200°C for Cu(Mo) 5 and pure Cu, respectively. This suggests the better thermal stability of the Cu(MoN x ) alloy film.…”
Section: Cu(mon X ) On Barrierless Simentioning
confidence: 75%
“…[2][3][4][5][6][7][8][9][10][11][12][13] Some have investigated the alloying of an insoluble substance (e.g., W 4 ) into Cu, which forms distinctive microstructures with good thermal properties on barrierless Si; these structures have valuable applications in materials science. Chu and Lin 12 reported an annealing method for Cu(WN)/Si by forming a self-passivated layer in order to improve the thermal stability of Cu films.…”
Section: Introductionmentioning
confidence: 99%